-14a+9=11a+12

Simple and best practice solution for -14a+9=11a+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -14a+9=11a+12 equation:


Simplifying
-14a + 9 = 11a + 12

Reorder the terms:
9 + -14a = 11a + 12

Reorder the terms:
9 + -14a = 12 + 11a

Solving
9 + -14a = 12 + 11a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-11a' to each side of the equation.
9 + -14a + -11a = 12 + 11a + -11a

Combine like terms: -14a + -11a = -25a
9 + -25a = 12 + 11a + -11a

Combine like terms: 11a + -11a = 0
9 + -25a = 12 + 0
9 + -25a = 12

Add '-9' to each side of the equation.
9 + -9 + -25a = 12 + -9

Combine like terms: 9 + -9 = 0
0 + -25a = 12 + -9
-25a = 12 + -9

Combine like terms: 12 + -9 = 3
-25a = 3

Divide each side by '-25'.
a = -0.12

Simplifying
a = -0.12

See similar equations:

| 4/7=2c | | 2n+b-3n=-6 | | f(x)=(x^2-3x-1)/x | | R^2-9/2r=29 | | 0=-16t^2+10t+56 | | -25+3x=0 | | 20n-19n+21=-21 | | x=4/3×3.14×7×7×7 | | 1/x^2-4=0 | | 15x-177=6x-6 | | 4x+4=3y+6 | | Log[9]5+log[9]4= | | 7.3=(2x)/(.3-x) | | X/5=x-7/7 | | 3/17x=-6 | | 15x^4+6x^2-18x^3= | | n/-1.8=2.1 | | 7x+8=9-(4x-9) | | -16x^2+1000x+3=9 | | 4x+y=225 | | -3=4w | | 3y-6=21x | | 7j+14=16 | | z=20*x | | X^1/2-8=0 | | 2x-2+6x-10=180 | | 4x+6=7x+12 | | 2-8(3-6x)=0 | | 4(x-3)=3-(x+5) | | x+3/5-7=2 | | 1.5cosx(0.5-cosx)=0 | | 7-5(2x+9)=4 |

Equations solver categories